KEUNGGULAN DIFERENSIASIF DAN KINERJA PEMASARAN - Ferdinand, Augusty (JURNAL BISNIS STRATEGI, 2003)
Company Specific Differentiation Advantage is conceived as the main thrust of most strategy directions in management practices within a company. As a firm is understood as a going concern, a company'sobjective is to generate and to sustain its marketing performance. The question then is: how does a firm generate and sustain its marketing performance? The answer might be found in the conceptualization of resources and capabilities, which are postulated as a basis for generating company specific differentiated advantage as a means for enhancing marketing performance. A strategic marketing model based on four main constructs comprising company social resources, company specific organisational capabilities, company specific differentiation advantage, marketing performance was developed. This model was tested successfully on Rural People Credit Banks of Indonesia.